COMMUNITY STRUCTURE OF MAKROZOOBENTHOS IN THE INTERTIDAL ZONE OF KARANG ISLAND, CENTRAL TAPANULI, NORTH SUMATERA - Sinaga, Andri Decshana; Mulyadi, Aras; Tanjung, Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Makrozoobenthos is a benthic animal measuring >500µm that lives on the bottom and surface of the water substrate. Makrozoobenthos community structure is influenced by changes in environmental factors. The reseach was conducted in August-November 2018 in the coastal waters of the Karang island of Sosorgadong District, Central Tapanuli Regency, North Sumatera Province.The aims of the research were to determine the structure of the makrozoobenthos community which includes species, abundance, diversity index, uniformity index and dominance index. Sampling used the line transect method at 3 stations. The results of the study found 5class makrozoobenthos consisting of 24 species. The abundance value obtained was in the range of 7-8 ind./m2. Diversity index values ranged from 1.07-1.48, which are classified as moderate, while the uniformity index value ranges from 0.72-0.91 which is balanced. The dominance index value ranged from 0.39-0.59, i.e there are species that dominate.Keywords: Makrozoobenthos, Community Structure, Karang Island